(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the impact of monetary policy transmission mechanisms on investment activity in developing economies. The study examines the effects of the central bank’s interest rate, money supply, inflation rate, and credit volume on investment activity. In addition, the processes through which monetary policy is transmitted to the economy via the interest rate channel, credit channel, and exchange rate channel are discussed from both theoretical and empirical perspectives.